From waste to wealth: Repurposing slaughterhouse waste for xenotransplantation - Khan, Raheema L.; Khraibi, Ali A.; Dumée, Ludovic F.; Corridon, Peter R. (Frontiers in Bioengineering and Biotechnology, 2023)
Slaughterhouses produce large quantities of biological waste, and most of these materials are underutilized. In many published reports, the possibility of repurposing this form of waste to create biomaterials, fertilizers, biogas, and feeds has been discussed. However, the employment of particular offal wastes in xenotransplantation has yet to be extensively uncovered. Overall, viable transplantable tissues and organs are scarce, and developing bioartificial components using such discarded materials may help increase their supply. This perspective manuscript explores the viability and sustainability of readily available and easily sourced slaughterhouse waste, such as blood vessels, eyes, kidneys, and tracheas, as starting materials in xenotransplantation derived from decellularization technologies. The manuscript also examines the innovative use of animal stem cells derived from the excreta to create a bioartificial tissue/organ platform that can be translated to humans. Institutional and governmental regulatory approaches will also be outlined to support this endeavor.